Astrocytoma - Fahrul Amri (Jurnal Kedokteran Syiah Kuala, 2009)
Abstnk.   Astrocytoma  merupakan  tumor otak yang  paling sering terjadi  pada anak, dengan frekuensi lebih dari setengah jumlah  keganasan pada sistem saraf primer.  Insidensi   tahunan  mencapai 14 kasus baru per 1000000 anak dibawah   usia 15   tahun.  Diagnosis ditegakkan berdasarkan gejala klinis, pemeriksaan fisik, pemeriksaan CT scan dan pemeriksaan Head and spine MRI.  Penanganan Astrocytoma disesuaikan dengan lokasi dan grade dari tumor tersebut.   IO.year survival rate untuk astrocytoma cerebellar low-grade yang dapat diangkat lengkap mendekati  100%.  (JKS 2009,·2:97-100)Kata Kunci :  AstrocytomaAbstract. Astrocytoma is the most common brain tumor of childhood, more than 50%  tumor on primary nervous system. Annual incident reach 14  new cases per 1:000.000   children under 15  years old, Diagnose is  made based on clinical   symptoms,  physical examination, CT Scan  and Head and Spine MRI.  Management of Astrocytoma  is based on the location and grade of the tumor.   IO-year   survival rate for low  grade Cerebellar Astrocytomas, which are resected completely,  is near 100%.   (JKS 2009;2:97-100)Key word : Astrocytoma